John Baldessari some stories ([S.l.] Media Art Services [distributor], 1990)
Presented without commentary, this film reveals the thinking behind the work of John Baldessari over the course of his career, and provides clues to the understanding of the artist's paintings, photographic work and books. What emerges is a portrait of a thoughtful, quietly rebellious artist who has influenced a large number of younger artists over the last twenty years, and who has clearly followed his own path in the exploration of the territory which he embarked upon in the late 60's.
VHS format.
Director and edited by Peter Kirby ; director of photography, Harry Dawson ; audio recordist, Gary Woods.
Keywords: Baldessari, John, 1931-.; Artists -- United States -- Interviews; Art -- American -- 20th century